SISTEM DIAGNOSA KEGAGALAN DALAM BUDIDAYA IKAN KONSUMSI AIR TAWAR DENGAN MENGGUNAKAN METODE CASE BASED REASONING - Reski Mai Candra (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
Freshwater fish cultivation is one of the goals to meet the needs of fish to be consumed, in addition to freshwater fish farming consumption can give time to marine biota to breed because at this time marine fishery has been overfishing. Case Based Reasoning (CBR) is a method used to build a knowledge-based system. Sources of system knowledge are obtained by collecting the handling of cases by an expert. In this study the authors implement CBR method to help the diagnosis of failure of goldfish cultivation. The cases used in the system are cases of failure of carp farming that have occurred before and the case will be used to solve the case in the future. The system will provide output in the form of a possible failure of goldfish cultivation and handling solutions based on the similarity of new cases with knowledge possessed by the system. This system is built with PHP programming language and MySQL database management system. Based on the tests that have been done the diagnostic system can provide the best solution recommendations on new cases based on the nearest previous case the level of similarity and there is no significant difference between the results issued by the system and experts.